THE SIGNIFICANCE OF DISCOURSE ANALYSIS IN LANGUAGE TEACHING AND LEARNING - siyaswati, siyaswati (Buana Pendidikan, 2013)
Discourse analysis is a general term for a number of approaches to analyze written, spoken, signed language use or any significant semiotic event. The objects of discourse analysis are writing, talk, conversation, communicative event, etc. To have a primary understanding on the discourse analysis in language teaching and learning, the writer hereby tries to descriptively discuss the significance of discourse analysis in language learning and teaching. Of course, this description cannot be claimed as the complete description of discourse analysis since discourse analysis is an ample topic that is applied in various disciplines. At least, however, this paper hopefully can give a highlight to step further.